2016
DOI: 10.1097/ajp.0000000000000347
|View full text |Cite
|
Sign up to set email alerts
|

Acute Low Back Pain

Abstract: Objectives Low back pain is the second most frequently diagnosed pain condition in the United States’ and although a majority of individuals have resolution of pain during the acute period, an estimated 40% of individuals will experience persistent pain. Given the heterogenous nature of low back pain, this study sought to describe and compare somatosensory and molecular (gene expression) profiles between individuals with acute low back pain and healthy no-pain controls Methods Using a previously established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 45 publications
5
33
1
Order By: Relevance
“…At baseline, pressure pain tests were similar between groups, which aligns with results from a previous prospective study in acute LBP 48 and other studies that reported no differences in PPT between acute LBP and healthy controls. 38 , 39 When the z -score plots (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…At baseline, pressure pain tests were similar between groups, which aligns with results from a previous prospective study in acute LBP 48 and other studies that reported no differences in PPT between acute LBP and healthy controls. 38 , 39 When the z -score plots (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Despite the lack of knowledge about the mechanism and origin of LBP, acute LBP participants seems to be influenced by selective pain sensitivity enhancement and differential gene expression profiles with regard to no-pain participants 23. Neuronal differences have been observed between depression and LBP 24.…”
Section: Discussionmentioning
confidence: 99%
“…The medial side of the nondominant forearm was utilized for testing purposes. The protocol is described in detail in a previous manuscript by our group (Starkweather et al, 2016).…”
Section: Pain Sensitivity Measuresmentioning
confidence: 99%